Management of Character Education Based on Panca Jiwa in Pondok Pesantren Darul Muttaqien Bogor - Odik Sodikin; Ujang Cepi Barlian; Sofyan Sauri; Dadan Nurulhaq (International Journal of Nusantara Islam, 2020)
The purpose of this study was to examine how the management of character education based on the five souls at Pondok Pesantren Darul Muttaqien Bogor. The method used in this research is descriptive method which aims to describe and describe the phenomena in the field, namely scientific phenomena. The results showed that the five souls as the foundation for character education in Islamic boarding schools contain five values, including the value of sincerity, simplicity, independence, ukhuwah Islamiyah, and the value of freedom. Where these five values must be practiced as much as possible so that the students become strong and tough Muslim personalities like buildings that have a solid foundation, and for those who can practice them well, it will be easy to meet the future as well as possible.